Performing Diplomatic Decorum: Repertoires of "Appropriate" Behavior in the Margins of International Diplomacy. Issue 4 (7th December 2018) - McConnell, Fiona
Abstract: This paper interrogates the notion of diplomatic decorum in order to shine new light on the power relations that underpin performance, rhetoric, and emotional labor in international politics. In framing decorum in terms of Aristotelian rhetoric and dramaturgical principles, the paper focuses on representatives of minority communities, indigenous peoples, and stateless nations for whom adopting social behavior appropriate for the spaces of international diplomacy takes on a heightened importance. Drawing on postcolonial critiques of diplomacy, attention turns to two distinct political repertoires and configurations of style and subject that these liminal geopolitical actors engage with. First the paper examines the extent to which "unofficial" diplomats perform behavior fitting to a particular diplomatic space and how they seek to enact a diplomatic style that will be deemed appropriate to their subject position as both outsiders and aspirant diplomats. Second, the paper examines what it means to break the unwritten rules of diplomatic decorum, both in terms of incidences where individuals push the boundaries deliberately in order to perform otherness, and in examples where diplomatic performances go awry. The paper concludes by considering the ways in which decorum is a productive lens through which to view and reassess the colonial norms and power relations underpinning diplomacy.